2017
DOI: 10.3390/ijms18020209
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Rice Laccase Gene (OsLAC) Family and Ectopic Expression of OsLAC10 Enhances Tolerance to Copper Stress in Arabidopsis

Abstract: Laccases are encoded by a multigene family and widely distributed in plant genomes where they play roles oxidizing monolignols to produce higher-order lignin involved in plant development and stress responses. We identified 30 laccase genes (OsLACs) from rice, which can be divided into five subfamilies, mostly expressed during early development of the endosperm, growing roots, and stems. OsLACs can be induced by hormones, salt, drought, and heavy metals stresses. The expression level of OsLAC10 increased 1200-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 55 publications
(86 reference statements)
7
88
1
Order By: Relevance
“…In addition, OsmiR397, OsmiR398 and OsmiR408 also play an important role in abiotic and biotic stress responses (Jia et al ., ; Lu et al ., ; Pan et al ., ). OsLAC8 and OsLAC29 were significantly induced by salt stress in both salt‐sensitive cultivars (Liu et al ., ). Therefore, we hypothesized that OsAGO17 may respond to stress in rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OsmiR397, OsmiR398 and OsmiR408 also play an important role in abiotic and biotic stress responses (Jia et al ., ; Lu et al ., ; Pan et al ., ). OsLAC8 and OsLAC29 were significantly induced by salt stress in both salt‐sensitive cultivars (Liu et al ., ). Therefore, we hypothesized that OsAGO17 may respond to stress in rice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, three LAC genes showed the same change in expression as OsLAC, and the expression patterns of these genes were complementary to that of OsAGO17. OsLAC14 is a homologue of OsLAC (Liu et al, 2017). Thus, OsLAC may not be the only target gene of OsmiR397b in the regulation of grain size, and OsAGO17 may affect grain size by regulating the expression of other LAC genes.…”
Section: Discussionmentioning
confidence: 99%
“…OsLAC13 regulated the seed setting rate in rice by suppressing the transport of sugars to the anthers and promoting H 2 O 2 production through unknown mechanisms (Yu et al, 2017). However, heterologous expression of OsLAC10 in Arabidopsis plants increased lignification around vasculature and increased Cu stress tolerance (Liu et al, 2017). Triple mutant of atlac4, atlac11 and atlac17 had very much reduced lignin deposition in the vasculature and the plants were dwarf (Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fast reddish-brown color formation, indicating oxidation of guaiacol ( Figure 1A), as well as the best activity of cell-free extracts in ABTS assay ( Figure 1B), three strains, namely P. putida Catalysts 2019, 9,629 3 of 14 F6, P. putida KT2440, and P. putida CA-3, were chosen for further study. Notably, cell-free extracts of P. putida F6 exhibited two times higher laccase activity (ABTS assay) compared to cell free extracts from P. putida KT2440 and P. putida CA-3, respectively, which showed a similar activity level ( Figure 1B).…”
Section: Screening For Laccase Activity Using Guaiacol Agar Plates Anmentioning
confidence: 99%
“…Laccases are blue multicopper enzymes (EC 1.10.3.2) that oxidize a broad range of both phenolic and non-phenolic substrates, via a four-electron reduction of molecular oxygen to water [1,2]. These enzymes are widely distributed in nature and have been isolated from bacteria [3][4][5], fungi [6,7] and plants [8,9], as well as from lichens [10], and sponges [11]. Although laccases are heterogeneous in different species, implying diversity in their function, four copper-binding motifs are conserved in the…”
Section: Introductionmentioning
confidence: 99%